Analisis Teori Tindakan Beralasan terhadap Intensi Imunisasi Tetanus Toksoid pada Mahasiswi Universitas X - Rifaldi Rifaldi; Rani Merlinda Saragih; Rayhanaddinoor Rahmah; Reni Saufi Jayanti; Rhizsa Niematoon Naem (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
The incidence of tetanus neonatorum is one of the causes of neonatal death in Indonesia that still requires serious attention. This disease can actually be prevented from an early age through the administration of tetanus toxoid immunization to women of childbearing age (WUS), especially premarital WUS as mother-to-be. Higher levels of education in premarital WUS are known to play a role in supporting the formation of intentions to carry out tetanus toxoid immunization. The intention of tetanus toxoid immunization in this study was studied based on the theory of reasoned action, which emphasizes the role of attitudes and subjective norms in shaping behavioral intentions. The purpose of this study is to analyze the intention of tetanus toxoid immunization in University X students based on the theory of reasoned action. This study is a correlative analytical research with the design of the cross-sectional study. The sample selection technique used accidental sampling so that 33 female respondents were obtained. The data was analyzed using the Spearman rho correlation test. The results showed a moderate and significant correlation between subjective norms (ρ=0.418; p=0.015) and attitudes (ρ=0.359; p=0.040) and tetanus toxoid immunization intention. Therefore, fostering a social atmosphere and environmental support is needed to strengthen the intention of tetanus toxoid immunization in premarital WUS.